2006
DOI: 10.1016/j.jqsrt.2005.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering by complex ice-analogue crystals

Abstract: Original article can be found at : http://www.sciencedirect.com/ Copyright ElsevierAngle-dependent light scattering measurements on single ice analogues crystals are described. Phase functions and degree of linear polarization are measured for electrodynamically levitated crystals. A procedure for randomizing particle orientation during levitation is demonstrated. The dependence of scattering on the shape, complexity and surface roughness of the crystals is examined. The phase functions from complex crystals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
109
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 9 publications
4
109
0
Order By: Relevance
“…The difference in reflected shortwave flux is at most about 7 W m 22 , assuming an area-averaged incident solar flux of 330 W m 22 , at least for the case considered here. These differences found for the g parameterizations are far less than the range in g found by several studies (Ulanowski et al 2006;Fu 2007;Garrett 2008;Baran 2012;van Diedenhoven et al 2014;Yang et al 2015). Indeed, in the case of Ulanowski et al (2006), experimentally derived g values were found to vary between 0.80 6 0.04 and 0.63 6 0.05 for smooth and rough ice analog rosettes, respectively, and this difference results in a shortwave flux uncertainty of about 256 W m 22 .…”
Section: The Parameterizationmentioning
confidence: 64%
See 4 more Smart Citations
“…The difference in reflected shortwave flux is at most about 7 W m 22 , assuming an area-averaged incident solar flux of 330 W m 22 , at least for the case considered here. These differences found for the g parameterizations are far less than the range in g found by several studies (Ulanowski et al 2006;Fu 2007;Garrett 2008;Baran 2012;van Diedenhoven et al 2014;Yang et al 2015). Indeed, in the case of Ulanowski et al (2006), experimentally derived g values were found to vary between 0.80 6 0.04 and 0.63 6 0.05 for smooth and rough ice analog rosettes, respectively, and this difference results in a shortwave flux uncertainty of about 256 W m 22 .…”
Section: The Parameterizationmentioning
confidence: 64%
“…These differences found for the g parameterizations are far less than the range in g found by several studies (Ulanowski et al 2006;Fu 2007;Garrett 2008;Baran 2012;van Diedenhoven et al 2014;Yang et al 2015). Indeed, in the case of Ulanowski et al (2006), experimentally derived g values were found to vary between 0.80 6 0.04 and 0.63 6 0.05 for smooth and rough ice analog rosettes, respectively, and this difference results in a shortwave flux uncertainty of about 256 W m 22 . Furthermore, the calculated asymmetry parameter values using the two parameterizations compare well against radiometrically derived asymmetry parameter values using POLDER observations from van Diedenhoven et al (2014).…”
Section: The Parameterizationmentioning
confidence: 64%
See 3 more Smart Citations